UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN METODE THINK PAIR SHARE - Dahlia, Dahlia (JURNAL PENA EDUKASI, 2018)
Abstract: This study aims to find an effective and efficient learning strategy in teaching integer material for students in the Elementary School Class, by activating students in learning. The strategy in classroom action research is carried out through 2 cycles and in each cycle includes activities of planning, implementation, observation and reflection. As for activating students in this study, researchers used worksheets given to students in large groups and small groups. The subject of this class action research is the fourth grade students of Public Elementary School 014687 Rawang Pasar IV in the District of Rawang Panca Arga in Asahan Regency in the first semester of 2017/2018 learning year, while the object is learning material for integer counting on Mathematics taught by way activate students in Think Pair Share learning. From the research conducted by examining the initial condition of students as measured by written test kits and the results of classroom action research with 2 cycles, there was an increase in the results achieved by students in mastering the integer material given. Increased mastery of this material starting from the first cycle of students can increase from the condition (6%) while the conditions in the first cycle (29%) after the action in cycle II completeness reached (94%). Keywords: Think Pair Share Abstrak: Penelitian ini bertujuan untuk mencari suatu strategi pembelajaran yang efektif dan Efisien dalam mengajarkan materi bilangan bulat bagi siswa di Kelas SD Negeri ,dengan cara mengaktifkan siswa pada pembelajaran. Strategi dalam penelitian tindakan kelas ini dilakukan melalui 2 siklus dan pada setiap siklus meliputi kegiatan perencanaan, pelaksanaan, observasi dan refleksi. Sedang untuk mengaktifkan siswa dalam penelitian ini, peneliti menggunakan lembar kerja yang diberikan kepada siswa dalam kelompok besar dan kelompok kecil. Yang menjadi subjek pada penelitian tindakan kelas ini adalah siswa kelas IV SD Negeri 014687 Rawang Pasar IV Kecamatan Rawang Panca Arga Kabupaten Asahan semester 1 pada tahun pembelajaran 2017/2018, sedang objeknya adalah pembelajaran materi pengerjaan hitung bilangan bulat pada mata pelajaran Matematika yang diajarkan dengan cara mengaktifkan siswa dalam pembelajaran Think Pair Share. Dari penelitian yang diadakan dengan meneliti kondisi awal siswa yang diukur dengan alat tes tertulis dan hasil penelitian tindakan kelas dengan 2 siklus terlihat adanya peningkatan hasil yang dicapai siswa dalam menguasai materi bilangan bulat yang diberikan. Peningkatan penguasaan materi ini mulai dari siklus I siswa dapat meningkat dari kondisi (6 %) sedang dari kondisi di siklus I (29%) setelah dilakukan tindakan pada siklus II ketuntasan mencapai (94 %). Kata Kunci: Think Pair Share